Medical Students' Perception about the Effectiveness of Interactive Session in Small Groups - Shazia Riaz, Ahmed Nurus Sami, Fareesa Waqar (Journal of Islamic International Medical College, 2015)
Objective: To find out the perception of undergraduate medical students about the effectiveness of interactive sessions in small groups. Study Design: A descriptive cross sectional study. Place and Duration of Study: This study was conducted at Islamic International Medical College Rawalpindi from 10 April th to 12 June 2014. Materials and Methods: A total of 100 students from 3rd and 4th year MBBS were enlisted on first come first basis out of those who volunteered to participate in the study. They were provided with questionnaire (Table I) to give their opinion about the effectiveness of interactive sessions in small groups as learning tool during undergraduate medical studies. Results: Out of the 100 participants 65% considered interactive small group discussions effective, 16.7% were indecisive, while 18.3% disagreed that interactive small group discussions were very effective at undergraduate level in medical education. In students' opinion sessions kept the students attentive (93%), promoted group interaction skills (95%) and promoted critical thinking (63%). A majority (76%) thought that there was good retention of the subject discussed in an interactive session. In students' opinion it gave them a good chance to evaluate them (71%). Conclusion: It is concluded that interactive group discussions is an effective method of imparting education to medical students at undergraduate level.